Indicators for economic vulnerability to drought in South Africa. Issue 8 (17th November 2017) - Mdungela, Nomalanga M.; Bahta, Yonas T.; Jordaan, Andries J.
ABSTRACT: This article identifies and estimates economic drought vulnerability indicators among communal farmers in South Africa, using an economic vulnerability index based on a household survey of 121 communal farmers. The results show that lack of resources, unemployment, price sensitivity, market access, the level of farm debt, output, on- and off-farm diversification, management, and financial safety nets were the main economic vulnerability variables. Farm debt and financial safety provide the bulk of the vulnerability index. The study's findings suggest that government should reconsider priorities in the implementation of appropriate policy measures in response to drought.